Study Experimental the Quality of Tombstones by Utilizing Coconut Fiber Using Seven Tools - Rosyidi, Moh Ririn; Narto (Spektrum Industri, 2022)
Product quality in the production process is important, where consumer needs for the quality of the products produced will be better or better by going through existing processes and innovations in products that can make products that were originally good become better. The quality improvement on the tombstones at UMKM_SADAR Gresik has problems in terms of unstable quality and there are defects with thin cracks, small at the corners. there are several factors that need to be considered, namely in the fish bone diagram on human factors, methods, materials, the environment, namely the need for skills training/training for the process of making the tombstone and adding raw materials by utilizing the addition of coconut fiber to improve quality in the compression test and can reduce the potential for thin cracks, chipping at the corners of tombstones and monitoring worker evaluations